Bioremediation of aquaculture wastewater using the fungal biomass integrating Plackett–Burman design - Hazem T. Abd El-Hamid; Muhammad A. El-Alfy; Hanan M. Hafiz; Hoda M. El-Gharabawy (Biodegradation, 2026)
Aquaculture wastewater contains elevated levels of nutrients and organic pollutants that can accelerate eutrophication and impair aquatic ecosystems if discharged untreated. In the study, a fungal-based remediation approach was investigated for the removal of pollutants from aquaculture wastewater collected from Baltim Station ponds (31.55244° N, 31.092855° E) near Lake Burullus, Egypt. Two native fungal isolates, Aspergillus niger and Aspergillus flavus , were employed for primary mycoremediation experiments, while Ganoderma mbrekobenum was included only in the Plackett–Burman experimental design to evaluate the influence of environmental and nutritional factors on total phosphorus (TP) removal under optimized conditions. The fungal treatment significantly improved water quality, showing substantial reductions in total protein, phosphorus, nitrogen, organic matter, and chemical oxygen demand (COD) indicating a vital role of Aspergillus species in the bioremediation of nutrient-rich aquatic environments. The Plackett–Burman design (PBD) showed that fungal treatment significantly reduced pollutant concentrations with higher metabolic activity and enzymatic production as dehydrogenase and total protein from 9 to 12 days. Moreover, PBD identified KH 2 PO 4 and MgSO₄ as the most influential variables for enhancing TP removal in the presence of G. mbrekobenum , while peptone and yeast extract exhibited the greatest effect in the non-fungal control system. The regression models demonstrated strong predictive accuracy (R 2 > 0.99), confirming the validity of the optimization approach. The results highlight the effectiveness of fungal biomass as a cost-effective and eco-friendly bioremediation strategy for mitigating nutrient pollution in aquaculture effluents and protecting sensitive aquatic environments such as Lake Burullus.